The Influence of Coping Toward Stress With Hyperthension Case at Public Health Center in Langsa Baro - Ajmain (Akademi Keperawatan Kesdam Iskandar Muda Lhokseumawe, 2021)
Hypertension is an abnormal increase in blood pressure. Increased blood pressure is a blood circulation disorder that does not cause the sufferer to die suddenly, yet hypertension can trigger the emergence of other very dangerous diseases such as heart attacks, strokes, kidney disorders, and even in patients with chronic hypertension it can cause death. Increased blood pressure is caused by many factors, one of which is stress. Psychological disorders (stress) that are prolonged can trigger an increase in blood pressure. The impact of this disease has caused a mortality rate of 9.4% worldwide every year. This study aims to see the extent of the effect of coping on stress with the incidence of hypertension. This research method is quantitative, with the type of analytic research, and is cross-sectional. The data used are primary data. The number of respondents was 77 people who were taken by Proportional Stratified Random Sampling using a questionnaire. The statistical test used is the Chi-Square test with an alpha of 0.05. The results showed that 52 (67.5%) respondents had hypertension, and 40 (51.9%) respondents had maladaptive coping. P-value (person Chi-Square) 0.027 (p>0.05). There is an effect of coping with stress on the incidence of hypertension. Puskesmas are expected to increase promotive and preventive efforts in order to help patients form adaptive coping mechanisms and implement stress management for patients with hypertension.